Leadership Styles and Attributes of Prominent Women Business Leaders: A Case Study (Journal of Business Management and Accounting, 2020)
Malaysia is encouraging the involvement and participation of women in developing its economy and in transforming it to become a developed nation by the year 2020. However, studies that look into the attributes of successful women business leaders are scarce. Hence, it is the focus of this paper to reveal the attributes of prominent women business leaders and their respective leadership styles. Three (3) prominent women business leaders from various industries participated in this study and data were gathered through qualitative semi-structured interviews. It was found that the attributes possessed by these participants are similar to their  male counterparts. The only differences between men and women business leaders are in terms of (i) the amount of focus time spent between domestic chores and work, and (ii) the motherly/sisterly approach portrayed by the participants, which is unique to women business leaders. The participants demonstrated three styles of leadership, namely paternalistic, transformational, and participative.